Impaired functional capacity in potential liver transplant candidates predicts short‐term mortality before transplantation. Issue 9 (4th August 2014) - Ow, Maggie M. G.; Erasmus, Paul; Minto, Gary; Struthers, Richard; Joseph, Moby; Smith, Aileen; Warshow, Usama M.; Cramp, Matthew E.; Cross, Tim J. S.
<x xml:space="preserve">Abstract</x> Liver transplantation (LT) is a lifesaving treatment. Because of the shortage of donor organs, some patients will not survive long enough to receive a transplant. The identification of LT candidates at increased risk of short‐term mortality without transplantation may affect listing decisions. Functional capacity, determined with cardiopulmonary exercise testing (CPET), is a measure of cardiorespiratory reserve and predicts perioperative outcomes. This study examined the association between functional capacity and short‐term survival before LT and the potential for CPET to predict 90‐day mortality without transplantation. A total of 176 patients who were assessed for nonacute LT underwent CPET. Ninety days after the assessment, 10 of the 164 patients who had not undergone transplantation were deceased (mortality rate = 6.1%). According to a comparison of survivors and nonsurvivors, the Model for End‐Stage Liver Disease score, UK Model for End‐Stage Liver Disease (UKELD) score, age, anaerobic threshold, and peak oxygen uptake (VO2) were significant univariate predictors of 90‐day mortality without transplantation, but only the UKELD score and peak VO2 retained significance in a multivariate analysis. The mean peak VO2 was significantly lower for nonsurvivors versus survivors (15.2 ± 3.3 versus 21.2 ± 5.3 mL/minute/kg, P < 0.001). According to a receiver operating characteristic (ROC) curve analysis, peak VO2 performed well as a diagnostic test (area under the ROC curve = 0.84, 95% confidence interval = 0.76‐0.92, sensitivity = 0.90, specificity = 0.74, P < 0.001). The optimal cutoff value for predicting mortality was ≤17.6 mL/minute/kg. The positive predictive value of a peak VO2 ≤ 17.6 mL/minute/kg for 90‐day mortality was greatest for patients with high UKELD scores: 38% of the patients with a UKELD score ≥ 57 and a peak VO2 ≤ 17.6 mL/minute/kg died, whereas only 6% of the patients with a UKELD score ≥ 57 and a peak VO2 > 17.6 mL/minute/kg died (P = 0.03). In conclusion, patients assessed for LT with an impaired functional capacity have poorer short‐term survival; this is particularly true for individuals with worse liver disease severity. Liver Transpl 20:1081–1088, 2014. © 2014 AASLD.